Gating modifier toxins reveal a conserved structural motif in voltage-gated Ca(2+) and K(+) channels - Li-Smerin, Yingying (National Academy of Sciences, 1998)
Protein toxins from venomous animals exhibit remarkably specific and selective interactions with a wide variety of ion channels. Hanatoxin and grammotoxin are two related protein toxins found in the venom of the Chilean Rose Tarantula, Phrixotrichus spatulata. Hanatoxin inhibits voltage-gated K(+) channels and grammotoxin inhibits voltage-gated Ca(2+) channels. Both toxins inhibit their respective channels by interfering with normal operation of the voltage-dependent gating mechanism. The sequence homology of hanatoxin and grammotoxin, as well as their similar mechanism of action, raises the possibility that they interact with the same region of voltage-gated Ca(2+) and K(+) channels. Here, we show that each toxin can interact with both voltage-gated Ca(2+) and K(+) channels and modify channel gating. Moreover, mutagenesis of voltage-gated K(+) channels suggests that hanatoxin and grammotoxin recognize the same structural motif. We propose that these toxins recognize a voltage-sensing domain or module present in voltage-gated ion channels and that this domain has a highly conserved three-dimensional structure.